2015
DOI: 10.1371/journal.pone.0125437
|View full text |Cite
|
Sign up to set email alerts
|

Low Abdominal NIRS Values and Elevated Plasma Intestinal Fatty Acid-Binding Protein in a Premature Piglet Model of Necrotizing Enterocolitis

Abstract: To identify early markers of necrotizing enterocolitis (NEC), we hypothesized that continuous abdominal near-infrared spectroscopy (A-NIRS) measurement of splanchnic tissue oxygen saturation and intermittent plasma intestinal fatty-acid binding protein (pI-FABP) measured every 6 hours can detect NEC prior to onset of clinical symptoms. Premature piglets received parenteral nutrition for 48-hours after delivery, followed by enteral feeds every three hours until death or euthanasia at 96-hours. Continuous A-NIRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…Adult rabbits had decreased liver oxygenation with SMA occlusion (7). Moreover, lower aNIRS correlated with the development of NEC in premature piglets (6,11). In our model, a significant correlation was evident between the change in aNIRS and the decrease in the perfusion from baseline.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Adult rabbits had decreased liver oxygenation with SMA occlusion (7). Moreover, lower aNIRS correlated with the development of NEC in premature piglets (6,11). In our model, a significant correlation was evident between the change in aNIRS and the decrease in the perfusion from baseline.…”
Section: Discussionmentioning
confidence: 90%
“…A previous study in premature piglets reported a difference in aNIRS saturations of 6.5% (standard deviation (SD): 4) between piglets with non-fulminant NEC and those with no NEC (6). Using these estimates, a sample size of seven would reject the null hypothesis that injured and non-injured piglets have similar aNIRS values at an alpha level of 0.05 and power of 0.8.…”
Section: Methodsmentioning
confidence: 98%
“…Combining NIRS with other modalities is a currently area of interest. Zamora et al 78 recently hypothesized that continuous abdominal NIRS monitoring combined with plasma I-FABP levels could identify NEC prior to the onset of clinical symptoms in premature piglets. In their study, I-FABP was confirmed to be a sensitive and specific indicator of NEC onset and severity.…”
Section: Update On Novel Imaging Methods—melissa Danko MD Eric Rellmentioning
confidence: 99%
“…described the transabdominal use of neonatal cerebral oximeters in a piglet model of NEC and found on post hoc analysis that low tissue oxygen saturations predicted the development of NEC. [7] In a separate paper from the same group, this finding was confirmed in neonates, though the significance of low saturations occurring days to weeks before the clinical onset of NEC was unclear. [8] Schat et al .…”
Section: Discussionmentioning
confidence: 94%